2018
DOI: 10.1093/carcin/bgy039
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin inhibits human breast cancer tumorigenesis by inducing cell death through the ROS-mediated RIP1/RIP3/PARP-1 pathways

Abstract: Bufalin, a key active ingredient of the Chinese medicine Chan Su, inhibits breast cancer tumorigenesis in vitro and in vivo. Here, we found that the pan-caspase inhibitor zVAD-fmk failed to inhibit bufalin-induced cell death in MCF-7 and MDA-MB-231 human breast cancer cells, confirming that the cell death induced by bufalin is caspase-independent. Instead, bufalin increased the expression of the necroptosis mediators RIP1 and RIP3. Bufalin-induced cell death was prevented by small molecule inhibitors of RIP1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 32 publications
1
48
1
Order By: Relevance
“…In addition, bufalin induces death in human cancer cells through the generation of reactive oxygen species, and induces necroptosis through the RIP1/RIP3/PARP-1 pathways. 11 From these findings, we believe that the microbubbles created by HIFU treatment may increase cell damage, especially to the mitochondria, resulting in the generation of reactive oxygen species. The increased reactive oxygen species induce apoptosis in the cancer cells through different pathways.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, bufalin induces death in human cancer cells through the generation of reactive oxygen species, and induces necroptosis through the RIP1/RIP3/PARP-1 pathways. 11 From these findings, we believe that the microbubbles created by HIFU treatment may increase cell damage, especially to the mitochondria, resulting in the generation of reactive oxygen species. The increased reactive oxygen species induce apoptosis in the cancer cells through different pathways.…”
Section: Discussionmentioning
confidence: 89%
“…Many studies have focused on the anticancer activities of bufalin, which have been proven to inhibit cell proliferation and angiogenesis, induce differentiation and apoptosis, reverse drug resistance, alter gene expression in tumor cells, and regulate the body's immune system. [11][12][13][14][15][16] In our previous studies, it was indicated that bufalin significantly inhibited the proliferation, invasion, and metastasis of hepatocellular carcinoma cells through the PI3K/AKT/mTOR/HIF-1α pathway. 17 However, there is no evidence to show whether bufalin could enhance the sensitivity of HIFU.…”
Section: Introductionmentioning
confidence: 98%
“…Although ROS-mediated necroptosis is harmful for the recovery of certain diseases, some researches also reported that it has the advantage on repressing the growth of tumor cells. Recently, Li et al revealed that ROS-mediated necroptosis repressed human breast cancer growth possibly due to impaired angiogenesis [56] . Ma et al reported mitochondrial ROS production induced by C/EBP homologous protein (CHOP) promoted A549 human lung cancer cell necroptosis and inhibited lung cancer progression [57] .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that inducing necroptosis could be used as a second-line treatment in cancer patients after the development of resistance to apoptosis [116][117][118]. Natural compounds such as shikonin (a component of a Chinese herbal medicine), staurosporine (an alkaloid extracted from the bacterium Streptomyces staurosporeus), neoalbaconol (a compound of a fungus), and bufalin (an ingredient of a Chinese medicine isolated from the skin and glands of toads) were also able to trigger necroptosis, with anti-tumoral outcomes [6,[119][120][121]. Recent results of some clinical studies confirmed that necroptosis promotes natural or therapy-driven anti-cancer immunosurveillance in different neoplasms, including breast and ovarian carcinoma [3].…”
Section: Necroptosis-based Therapies For Cholangiocarcinomamentioning
confidence: 99%